INTERNAL CORPORATE GOVERNANCE AND ORGANISATIONAL PERFORMANCE: EVIDENCE FROM INDONESIA - Wibowo, Amin; Evans, Robert; Quaddus, Mohammed (The journal of contemporary issues in business and government, 2009)
Despite the growing awareness, in many studies of organisational performance, of the importance of corporate governance, the majority of these studies have been based upon archival data from developed countries with one-tier board systems and have focused on governance structures rather than their performance. This study develops a measure of internal corporate governance based on managers’ assessment of the extent to which governance processes are effectively enacted. Reporting the responses of a sample of 496 managers of companies in Indonesia, where two tier boards are the norm, the study reveals that effective internal corporate governance mechanisms are only weakly associated with improved organisational performance.